PENGARUH PENGGUNAAN MEDIA FLASH CARD BERBASIS TEMA PROFESI TERHADAP PERKEMBANGAN BAHASA TULISAN ANAK KELOMPOK B - Sheri Alma, Yuandita; Musaddat, Syaiful; Rachmayani, Ika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Language development is one of the essential aspects of early childhood education that needs to be optimally stimulated through the use of engaging learning media that are appropriate to children's characteristics. The results of the preliminary observation at TK Negeri 2 Praya indicated that the language development of Group B children had not yet developed optimally, as reflected in their limited vocabulary and low ability to recognize letters and language symbols. This study aimed to determine the effect of profession-themed flash card media on the language development of Group B children at TK Negeri 2 Praya in the 2025/2026 academic year. The study employed a quantitative approach using a pre-experimental method with a One-Group Pretest–Posttest Design. The sample consisted of 20 Group B children selected through a simple random sampling technique. Data were collected through observation and documentation using a checklist instrument that had been validated through a content validity test using the Gregory Formula, yielding a validity coefficient of 0.815 (very high category). The data were analyzed using the Shapiro–Wilk normality test and the Paired Sample t-test. The findings revealed an increase in the mean score from 47.85 (pretest) to 77.15 (posttest), with a calculated t value of 278.700 and a significance value of 0.000 (2-tailed, p < 0.05). Therefore, it can be concluded that the use of profession-themed flash card media has a positive and significant effect on the language development of Group B children and can serve as an effective, engaging, and appropriate learning medium to support the implementation of the Merdeka Curriculum in early childhood education.